Childhood trauma and the role of self-blame on psychological well-being after deployment in male veterans. Issue 1 (1st January 2019) - Dorresteijn, Sasja; Gladwin, Thomas Edward; Eekhout, Iris; Vermetten, Eric; Geuze, Elbert
ABSTRACT: Background : Childhood trauma and combat-related trauma are both associated with decreased psychosocial functioning. Coping strategies play an important role in the adjustment to traumatic events. Objective : The present study examined childhood trauma and the mediating role of coping strategies in adult psychological symptoms in a non-clinical military population after deployment to Afghanistan. Additionally, the moderating role of coping strategies in vulnerability to combat events was explored. Method : Participants ( N = 932) were drawn from a prospective study assessing psychological complaints (SCL-90), early trauma (ETISR-SF), combat-related events and coping strategies (Brief COPE). Mediation analyses via joint significance testing and moderation analyses were performed. Results : Childhood trauma is related to adult symptoms of general anxiety, depression and problems concerning interpersonal sensitivity through the mediation of self-blame as a coping strategy. Some evidence was found that self-blame moderated vulnerability to combat-related events resulting in psychological complaints, specifically symptoms of anxiety and depression. Conclusions : Military personnel should be made aware of self-criticizing maladaptive belief systems when dealing with aversive events. Negative beliefs about oneself and distorted trauma-related cognitions may have a basis in childhood events. Self-blame cognitions may be a potential mechanism of change in empirically supported trauma interventions such as cognitive processing therapy.